Chronic Pain and Praying to a Higher Power: Useful or Useless? - Andersson, Gerhard (Journal of religion and health, 2008)
In the present study a Swedish sample of 118 persons with chronic pain completed online tests on two occasions in association with treatment trials. A three item subscale measuring praying as a coping strategy was derived from the Coping Strategies Questionnaire (CSQ), but adapted to refer to "a higher power" instead of "God". Measures of pain and anxiety/depression were also included. Results revealed significant associations between praying and pain interference and impairment. Praying was also associated with anxiety and depression scores. Results also showed that prayer predicted depression scores at follow-up, and that follow-up prayer was predicted by pain interference at first measurement occasion. Overall, if prayer had any relation with the other variables it was in the negative direction of more distress being associated with more praying both concurrently and prospectively.